Pyrazoline Derivatives as Promising MAO-A Targeting Antidepressants: An Update - Choudhary, Diksha; Kaur, Rajwinder; Singh, Thakur G.; Kumar, Bhupinder (Current Topics in Medicinal Chemistry, 2024)
Depression is one of the key conditions addressed by the Mental Health Gap Action Programme (mhGAP) of WHO that can lead to self-harm and suicide. Depression is associated with low levels of neurotransmitters, which eventually play a key role in the progression and development of mental illness. The nitrogen-containing heterocyclic compounds exhibit the most prominent pharmacological profile as antidepressants. Pyrazoline, a dihydro derivative of pyrazole, is a well-known five-membered heterocyclic moiety that exhibits a broad spectrum of biological activities. Many researchers have reported pyrazoline scaffold-containing molecules as potential antidepressant agents with selectivity for monoamine oxidase enzyme (MAO) isoforms. Several studies indicated a better affinity of pyrazoline-based moiety as (monoamine oxidase inhibitors) MAOIs. In this review, we have focused on the recent advancements (2019-2023) in the development of pyrazoline-containing derivatives exhibiting promising inhibition of MAO-A enzyme to treat depression. This review provides structural insights on pyrazoline-based molecules along with their SAR analysis, in silico exploration of binding interactions between pyrazoline derivatives and MAO-A enzyme, and clinical trial status of various drug molecules against depression. The in-silico exploration of potent pyrazoline derivatives at the active site of the MAOA enzyme will provide further insights into the development of new potential MAO-A inhibitors for the treatment of depression.
Keywords: Mental health